Alternatif Media for Fungal Growth Using a Different Source of Carbohidrats - Nurul Aini; Triastuti Rahayu (Universitas Sebelas Maret, 2015)
Fungi needs utrient, a source of energy and certain environmental conditions in order to growth. PDA was a common medium used to grow fungi in laboratories. The high of instant media PDA encourage researchers to find out alernatif media of the raw materials was easily available and more cheap. This researche determine the fungal growht in alternative media on carbohydrate source of the Canna edulis, Dioscorea aculeata and Maranta arundinacea. This study was an experimental studi using Completely Randomize Design (CDR), two factor. The first factor is a type of fungi: Candida albicans (J1), Aspergillus niger (J2). The second factor was the types of alternative media: the media of Canna edulis (M1),Discorea esculenta (M2) and Maranta arundinaceae L (M3). The collected data is analized by using qualitative descriptive. In this research Candida albicans was tested by spread method at 28oC for 2 days, Aspergillus niger by agar block method was tested at 30oc for 7 days. The result show that growth of Candida albicans best on medium Canna edulis with a population of 2,87×108CFU/ml and the size of fungal colony was large white, while the growth of Aspergillus niger best on medium Canna edulis with a diameter about 39,7 mm and heavy sporulation. Both of fungi test showed that almost comparable growth of PDA. Media Canna edulis, Dioscorea aculeata and Maranta arundinacea can be used as alternatives media for fungal growth. Keyword: fungal growth media, fungal, the source of carbohydrates, PDA.